Pengaruh orientasi pasar dan inovasi produk terhadap daya saing dan kinerja pemasaran pada UKM di Jakarta - Tannyago, Stefani; Widoatmodjo, Sawidji (Jurnal Manajemen Bisnis dan Kewirausahaan, 2025)
This study investigates the influence of market orientation and product innovation on marketing performance, with competitiveness as a mediating variable, among Small and Medium Enterprises (SMEs) in the food and beverage (FnB) sector in Jakarta. The research was motivated by the intense competition and rapidly changing consumer preferences that require SMEs to strengthen their marketing strategies through innovation and market responsiveness. The study aims to determine how market orientation and product innovation affect marketing performance directly and indirectly through competitiveness. Using a quantitative research design, data were collected from 162 SME owners and managers through questionnaires. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that both market orientation and product innovation have positive and significant effects on marketing performance. Product innovation also shows a significant positive influence on competitiveness, while market orientation has a positive but not significant effect on competitiveness. Furthermore, competitiveness significantly mediates the relationship between product innovation and marketing performance. These findings highlight the importance of continuous innovation and competitive strategies for SMEs to enhance marketing effectiveness and sustain growth in the dynamic FnB industry. The study contributes to understanding strategic marketing development in SMEs and provides implications for improving competitiveness and market adaptation.